Penerapan Model Collaborative Learning Untuk Meningkatkan Critical Thinking Skill Pada Siswa Sekolah Dasar - Ika Nur Laela; Meylinda Nurlatifah; Nabila Zahra Atika; Restina Salsabila Eka W; Uut Septiana (Lembaga Pengembangan Kinerja Dosen, 2024)
Collaborative learning is learning that involves students by forming small groups that work together to solve problems that aim to encourage students to play an active role and be able to think critically during learning. The characteristics of the collaborative learning model are considered to be able to train students' stimulus so that it can train and improve students' critical thinking skills. Collaborative learning is expected to be able to improve thinking skills and high thinking skills, especially critical thinking skills. Based on the results of the articles we have reviewed, it shows that collaborative learning that is applied can significantly provide benefits in improving thinking skills. However, there are some challenges that must be addressed such as time management of collaborative learning implementation and ensuring that all students get the same opportunity as other students.